A RECIPE FOR JUMP-LIKE PROGRESS IN SCIENCE – ILLUSTRATED BY 6 EXAMPLES - Otto E. Rossler; Ivan Zelinka (European Scientific Journal, ESJ, 2014)
Does there exist a method to boost scientific and humanitarian progress? Six cases in point are offered. The featured protagonists are: Zwicky, Einstein, Conrad, Reichardt, Szilard and Everett. The six breakthroughs offered are: (1) stationary cosmology (combined with a promising terrestrial fusion technology); (2) global-cgeneral relativity; (3) well-stirred life; (4) Pandaka-pygmaea based brain science; (5) an interactively reared wiser biological intelligence; (6) an experiment proving personalized assignment of the physical world.